Glycolysis Is Dynamic and Relates Closely to Respiration Rate in Stored Sugarbeet Roots - Megguer, Clarice A.; Fugate, Karen K.; Lafta, Abbas M.; Ferrareze, Jocleita P.; Deckard, Edward L.; Campbell, Larry G.; Lulai, Edward C.; Finger, Fernando L. (Frontiers in Plant Science, 2017)
Although respiration is the principal cause of the loss of sucrose in postharvest sugarbeet (Beta vulgaris L.), the internal mechanisms that control root respiration rate are unknown. Available evidence, however, indicates that respiration rate is likely to be controlled by the availability of respiratory substrates, and glycolysis has a central role in generating these substrates. To determine glycolytic changes that occur in sugarbeet roots after harvest and to elucidate relationships between glycolysis and respiration, sugarbeet roots were stored for up to 60 d, during which activities of glycolytic enzymes and concentrations of glycolytic substrates, intermediates, cofactors, and products were determined. Respiration rate was also determined, and relationships between respiration rate and glycolytic enzymes and metabolites were evaluated. Glycolysis was highly variable during storage, with 10 of 14 glycolytic activities and 14 of 17 glycolytic metabolites significantly altered during storage. Changes in glycolytic enzyme activities and metabolites occurred throughout the 60 d storage period, but were greatest in the first 4 d after harvest. Positive relationships between changes in glycolytic enzyme activities and root respiration rate were abundant, with 10 of 14 enzyme activities elevated when root respiration was elevated and 9 glycolytic activities static during periods of unchanging respiration rate. Major roles for pyruvate kinase and phosphofructokinase in the regulation of postharvest sugarbeet root glycolysis were indicated based on changes in enzymatic activities and concentrations of their substrates and products. Additionally, a strong positive relationship between respiration rate and pyruvate kinase activity was found indicating that downstream TCA cycle enzymes were unlikely to regulate or restrict root respiration in a major way. Overall, these results establish that glycolysis is not static during sugarbeet root storage and that changes in glycolysis are closely related to changes in sugarbeet root respiration.